Predictors of Poor Outcome Despite Successful Mechanical Thrombectomy of Anterior Circulation Large Vessel Occlusions Within 6 h of Symptom Onset - Mohammaden, Mahmoud H.; Stapleton, Christopher J.; Brunozzi, Denise; Hussein, Ahmad E.; Khedr, Eman M.; Atwal, Gursant; Alaraj, Ali (Frontiers in Neurology, 2020)
Background and Purpose Successful reperfusion is a significant predictor of a good clinical outcome after mechanical thrombectomy (MT). However, some patients have a poor clinical outcome even with successful reperfusion. We aimed to study factors that predict a poor clinical outcome (90-day modified Rankin Scale ≥ 3) in patients with anterior circulation large vessel occlusion (LVO) treated by successful MT within 6 hours of symptom onset. Methods We performed a retrospective review of a prospectively maintained MT database of all patients who underwent MT within 6 hours of symptom onset for an anterior circulation LVO at our institution from May 2016-June 2018. Uni- and multivariable analyses were performed to identify predictors of poor outcome. Results A total of 56 patients met the criteria for inclusion in this study. A poor outcome occurred in 31 (55.4%) patients. On univariate analysis, compared to patients with good clinical outcome, patients with poor outcome had higher mean baseline NIHSS scores (23.3 vs. 13.8, P<0.001), were more likely to have internal carotid artery (ICA) occlusions (38.7% vs. 8%, P=0.008), and had a higher incidence of distal clot migration (DCM) (48.4% vs. 8%, P=0.028). Age, gender, other baseline clinical characteristics, MT technique, and incidence of hemorrhagic transformation did not differ between the two cohorts. On multivariable regression analysis, baseline NIHSS score (OR;1.3, 95%CI [1.11-1.52], P=0.001), site of occlusion (ICA) (OR;8.9, 95%CI [1.3-60.9], P=0.026(, and DCM (OR;5.77, 95%CI [1.09-30.69], P=0.04) were independent predictors of poor outcome at 90-days. Conclusion Baseline NIHSS score, ICA occlusion, and DCM are independent predictors of a poor outcome after MT for anterior circulation LVO performed within 6 hours of symptoms onset.